Discussion on time resolution effect on the matching of PV generation and demand based on mean and variance. - Martín-Rivas, Sebastián; Sarria-Agis, Juan Antonio; Aguado-Sánchez, José Antonio (IEEE, 2022)
The effect of the time resolution of demand and photovoltaic (PV) generation on the matching of those profiles for a domestic installation is discussed based on mean and variance of the data profiles. A theoretical model is proposed and confronted with real data. It is studied how mean and variance of the data profiles, and the errors in the calculation of self-consumption and PV surplus are related to the data time resolution. Then those errors are related to mean and variance. And finally it is discussed how mean and variance are related to the installation features, as rated PV capacity, and consumption patterns.
Keywords: Energía fotovoltaica; Energía eléctrica - Distribución; Demand; PV generation; Time resolution; Mean; Variance